Facile synthesis of nickel nanowires with controllable morphology - Ying, Ying Kong; Suk, Fun Chin; Suh, Cem Pang (Elsevier B.V, 2015)
Nickel nanowires of controllable morphology were synthesized by a facile wet chemical reduction method using hydrazine hydrate as the reducing agent. Synthesis parameters such as reaction temperature, concentration of nickel ions, and pH of reaction medium were observed to have significant effects on the morphology of nickel nanowires formed. Only randomly aggregated nanoparticles were obtained at the reaction temperature of 30 1C. However, visibly defined nickel nanowires of longitudinally aligned nanoparticles, and fully transformed, well-defined long and slender nanowires were obtained at reaction temperatures of 60 1C and 120 1C, respectively. Higher reaction temperature led to the formation of nickel nanowires of decreasing mean diameters, whereas increasing initial concentration of nickel ions resulted in the formation of nickel nanowires of larger mean diameters. Besides, welldefined nickel nanowires were formed at the reaction medium pH of 4–5. Henceforth, the morphology of nickel nanowires could be modulated readily via precise control of the synthesis parameters such as reaction temperature and initial concentration of nickel ions. Nickel nanowires of tailored morphology could potentially be useful for the fabrication of nanowire-based electronic or electrochemical devices.